Inducible expression of the gene of Zinnia elegans coding for extracellular ribonuclease in Nicotiana tabacum plants - E. A. Trifonova; A. V. Romanova; S. S. Sangaev; M. V. Sapotsky; V. I. Malinovsky; A. V. Kochetov (Biologia Plantarum, 2012)
The gene of Zinnia elegans L. coding for S-like extracellular ribonuclease (ZRNase II) was used to produce transgenic tobacco plants with an increased ribonuclease activity. The protein-coding part of ZRNase II included the signal peptide sequence so the transgenic protein was located extracellularly. The cDNA of ZRNase II was cloned under the control of 2'-promoter of the mannopine synthase (MAS 2') gene from Ti-plasmid of Agrobacterium tumefaciens. It was shown that the resultant transgenic plants had an increased ribonuclease activity of the crude extracts and the induction of MAS 2' promoter by wounding additionally increased the activity. The plants of two transforming lines characterized by different ribonuclease activities were used to analyze the transgene influence on plant resistance to tobacco mosaic virus. The plants demonstrated either absence of disease symptoms or a significant delay in their appearance, depending on the virus content in the inoculum and ribonuclease activity.